# 1

2

3

Start P1 P2

Finish

 ∆x =
∆x =

4

C 5m 4m A

θ
3m

B

θ=

=

o

5

5m

A

C

2m

B

6

5m

A

B

7

x–t
x
Uniform motion

   x x x  vav   t t t
t ⇒

0 x
Non uniform motion

⇒ 0 x t

Non uniform motion

⇒ 0 t
8

v

xt

∆x v= ∆t
v

t

 x

 ∆x v= ∆t

v =

∆t →

  ∆x dx = ∆t dt
9

 vav

  ∆x v av = ∆t

x
x–t

∆x ∆t
0 x–t t

=

∆x ∆t

10

 v
x

v=

∆t →

∆x dx = ∆t dt
∆x t O

x–t

11

R 5m 4m P

θ
3m

Q

θ= θ=
o

12

Speed 20

Velocity 20 Stone is going up time

0

0
-20

time Stone is going down

13

v–t
v
Uniform motion

   v v v  aav    t t t
t v

0

Non uniform motion

⇒ 0 v t

Non uniform motion

0

t

14

15

 aav
 a av  ∆ v = ∆ t

16

v – t, v

 aav
v

0

t ⇒

0

t ⇒

 aav

 aav
17

v v –t

 a

t 

  v dv  t dt

v
t

18

a–t
a
Uniform motion

a 0 a t

Non uniform motion

a 0 a t

Non uniform motion

t 0

a

19

v
B

A

E C D

t

v v⇒ vv⇒ v , changed direction(-v) ⇒ v , changed direction(-v) ⇒
20

v B 20 C

A 0 4 10

D 12

t

v-t

21

xt

xt
x v  t t 

22

v a   t

v v va v v

a a   

    

23

∆x = x − x

   ∆x = x − x

∆x v= ∆t

  ∆x v= ∆t

  ∆v a= ∆t

24